Respuesta :

[tex]\bf \cfrac{3\pm1}{\frac{1}{3}}\implies \begin{cases} \cfrac{3+1}{\frac{1}{3}}\\\\ \cfrac{3-1}{\frac{1}{3}} \end{cases}\\\\ -------------------------------\\\\[/tex]

[tex]\bf \cfrac{3+1}{\frac{1}{3}}\implies \cfrac{4}{\frac{1}{3}}\implies \cfrac{\frac{4}{1}}{\frac{1}{3}}\implies \cfrac{4}{1}\cdot \cfrac{3}{1}\implies \cfrac{4\cdot 3}{1\cdot 1}\implies \cfrac{12}{1}\implies \boxed{12} \\\\\\ \cfrac{3-1}{\frac{1}{3}}\implies \cfrac{2}{\frac{1}{3}}\implies \cfrac{\frac{2}{1}}{\frac{1}{3}}\implies \cfrac{2}{1}\cdot \cfrac{3}{1}\implies \cfrac{2\cdot 3}{1\cdot 1}\implies \cfrac{6}{1}\implies \boxed{6}[/tex]